New Exact Iterative Method for the Capacitated Vehicle Routing Problem - Borcinova, Zuzana; Pesko, Stefan (Communications - Scientific letters of the University of Zilina, 2016)
The aim of the Capacitated Vehicle Routing Problem is to find a set of minimum total cost routes for a fleet of capacitated vehicles, to serve a set of customers. This problem belongs into category of NP hard problems that can be exactly solved only for small instances. In this paper we propose an exact iterative method for the CVRP based on the solution of Mixed Linear Programming model, which is able to solve problem for relatively larger instances in acceptable computing time.